Transducer for in bone stress and remodelling measuring. (December 2021) - Volf, Jaromír; Novák, Viktor; Ryženko, Vladimír; Bezouška, Vladimír; Bláhová, Marie
Abstract: This paper attends to new special transducer for measuring the stress field in the bone and its remodelling. This transducer is designed as hole that is placed into the bone. Needle sensor is complemented by optical fibre part with special LED light for bone remodelling measurement. The paper describes the design of this transducer, its properties and results of measurement, needle sensor simulation conditions and its calibration.